USE OF THE CONTENT ANALYSIS METHOD IN TEACHING THE SCIENCE OF HISTORY - Khusainbekova Culchira (American Journals, 2024)
This article describes the advantages of content analysis in teaching history in higher education, quantitative and qualitative analyzes aimed at determining the relationship between the content, form and communicative functions of the text.
Keywords: Content analysis, science of history, technology, semantic, communicative, unsystematic, random, historical.